Development of an Electronic Worksheet Oriented to Problem-Based Learning to Improve Metacognitive Skills on Reaction Rate Material - El Safitri, Nimas Ayu; Hidayah, Rusly (Jurnal Pijar Mipa, 2024)
Metacognitive skills are cognitive controls directly related to higher-order thinking processes, which are the demands of the Merdeka Curriculum. One of the efforts that can be used to improve metacognitive skills is to use learning media, namely Electronic Worksheets (E-Worksheets), oriented to Problem-Based Learning (PBL). This study aims to develop a feasible PBL-oriented E-Worksheet with valid, practical, and effective criteria to improve metacognitive skills on reaction rate material. This research model is guided by a 4D model (Define, Design, Develop, and Disseminate), which is limited to the development stage (Develop) with a limited trial to 30 SMA Negeri 21 Surabaya students. The research data showed that the validity of the E-Worksheet was declared valid in terms of the construct validity mode score of 4 with a suitable category, content validity of 4 with a good category, and graphics of 4 with a good category. The practicality of the E-Worksheet is stated to be practical based on the results of the students' response questionnaire, which obtained an average percentage of 96.17% in the very good. The effectiveness of the E-Worksheet is reviewed from the Pretest-Posttest N-gain value of metacognitive skills in the planning skills component, monitoring which successively gets a value of 0.84, 0.76, and 0.74 with high criteria. Based on this, it can be concluded that the developed E-Worksheet is feasible based on valid, practical, and effective criteria for improving metacognitive skills on reaction rate material.